Poloxamer 188-mediated anti-inflammatory effect rescues cognitive deficits in paraquat and maneb-induced mouse model of Parkinson's disease. (30th April 2020) - Ding, Wenbin; Lin, Hongyan; Hong, Xin; Ji, Dongliang; Wu, Feng
Abstract: Mild cognitive impairment in Parkinson's disease (PD-MCI) is considered as a nonmotor clinical symptom in Parkinson's disease (PD). Microglia-mediated inflammation contributes to cognitive function impairment. Poloxamer 188 (P188) is an amphipathic polymer which has cytoprotective effect in 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-induced dopaminergic (DA) neurons degeneration in PD. But whether P188 could ameliorate cognitive impairment in PD is still illusive. In the present study, we showed in a mouse model that paraquat (10 mg/kg) and maneb (30 mg/kg) (P + M) treatment intraperitoneally twice a week for 6 consecutive weeks resulted in cognitive deficits and synapse loss in hippocampus, together with DA neuron damage in the substantia nigra pars compacta (SNpc). P188 (0.8 g/kg) injection via tail vein 30 min after P + M administration significantly restored DA neuron numbers in SNpc and synapse density in hippocampus, and alleviated P + M-mediated cognitive function impairment in novel object recognition task and morris water maze task (MWM). Pathological synapse loss might be attributed to increased microglial phagocytic activity and cell density, and P188 prevented P + M-induced phagocytic state changes of microglia, such as increase in cell body size and decrease in process length, and upregulated microglia abundance in hippocampus. Consistently, P188 attenuated P + M-mediated increased mRNA levels of microglia proliferation related CSF1r and CSF2ra, microglial engulfment associated CD68, ICAM1, and ICAM2, and pro-inflammatory IL-6, IL-1β, CD11b, and TNF-α in hippocampus. Together, these findings suggest that the biocompatible polymer P188 blunts microglia activation which may promote synaptic loss and exacerbate cognitive function in a mouse model of PD-MCI.